Analisis Yuridis Pembuktian Tindak Pidana Narkotika Melalui Metode Undercover Buy - Marly Meani Silalahi; Dewi Romantika Tinambunan; Johan Pardamean Simanjuntak; Manotar Sinaga; Murniwati Lase; Parlaungan Siahaan; Dewi Pika Lumbanbatu (UPT Publikasi Ilmiah Unisba, 2025)
Narcotics crime in Indonesia is considered an extraordinary offense due to its severe social impact. Conventional evidentiary methods are often inadequate to uncover closed distribution networks, prompting Law No. 35 of 2009 on Narcotics to authorize special techniques such as undercover buy and controlled delivery. This study analyzes the evidentiary strength of narcotics cases proven through undercover buy and its implications for the principle of due process of law. The assumption is that valid evidence must not only meet the categories of Article 184 of the Criminal Procedure Code but also be obtained through legitimate and proportional procedures that respect human rights. Using a juridical-empirical method, the research combines normative legal analysis with case studies of court decisions and enforcement practices. The findings show that evidence from undercover buy can be admitted if supported by warrants, documentation, and secure chain of custody, though inconsistent practices and judicial interpretations still pose challenges.